Functional antimicrobial coatings for application on microbiologically contaminated surfaces. (2nd January 2021) - Pulit-Prociak, Jolanta; Staroń, Anita; Staroń, Paweł; Chwastowski, Jarosław; Kosiec, Aleksandra; Porębska, Halina; Sikora, Elżbieta; Banach, Marcin
ABSTRACT: Increases in diseases caused by pathogenic microorganisms and their growing resistances to antibiotics rise the need for the development of new antimicrobial materials. Silver nanoparticles exhibit high levels of antimicrobial activity. Compositions based on poly (vinyl alcohol) with different nanosilver contents were obtained and analysed. Materials differed in both the content of functional substances and their preparation parameters Research techniques, including spectrophotometry (UV-Vis) dynamic light scattering (DLS), Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), and transmission electron microscopy with an energy-dispersive X-ray spectrometer (TEM-EDX), were applied. The rheological properties of the compositions were tested. They may qualify as non-Newtonian, pseudoplastic fluids. Analyses of the forces needed to tear the adhesives were used to assess the adhesion properties. The antimicrobial properties against an Aspergillus niger strain are discussed. Concerning the bioavailability, the results revealed that, when the composition contacted amodel dermal membrane, the nanoparticles were unable to penetrate it.